2016
DOI: 10.1080/15222055.2016.1150923
|View full text |Cite
|
Sign up to set email alerts
|

Ploidy Variation and Viability of Aneuploid Ornamental Koi Carp Obtained by Crossing Triploid Females with Diploid Males

Abstract: Results of crossing triploid females of ornamental koi, a variant of Common Carp Cyprinus carpio, with diploid koi males in two consecutive spawning seasons (2014 and 2015) are presented. A total of seven progenies from six triploid females (one female was spawned twice) were produced and analyzed. The same as normal diploid females, triploid females were highly fertile and produced hundreds of thousands of eggs (up to 400,000 per female). Processes of embryo incubation and hatching of larvae in progenies obta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
22
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 10 publications
(22 citation statements)
references
References 6 publications
0
22
0
Order By: Relevance
“…Triploid males frequently produce aneuploid spermatozoa, whereas triploid females in most species are sterile (Benfey, ). However, triploid common carp Cyprinus carpio females have been found to produce aneuploid oocytes (Gomelsky, Delomas, & Warner, ; Gomelsky, Schneider, Anil, & Delomas, ). Triploidy is induced by applying a physical shock (temperature or pressure) to fertilized oocytes, which causes retention of the second polar body.…”
Section: Introductionmentioning
confidence: 99%
“…Triploid males frequently produce aneuploid spermatozoa, whereas triploid females in most species are sterile (Benfey, ). However, triploid common carp Cyprinus carpio females have been found to produce aneuploid oocytes (Gomelsky, Delomas, & Warner, ; Gomelsky, Schneider, Anil, & Delomas, ). Triploidy is induced by applying a physical shock (temperature or pressure) to fertilized oocytes, which causes retention of the second polar body.…”
Section: Introductionmentioning
confidence: 99%
“…Oshima et al (2005) reported the spawning of a few diploid eggs in natural triploid loaches. A similar shift of the modal ploidy level toward 2.6n-2.7n was recently reported in the progenies of fertile induced triploid ornamental carp (Gomelsky et al 2015). This is presumably explained by selective mortality against eggs during oogenesis and the resultant zygotes (embryos) \2.5n.…”
Section: Discussionmentioning
confidence: 58%
“…In several auto-and allotriploid fishes, which were artificially induced by inhibiting the second polar body release just after fertilization, gametes with a ploidy level of approximately 1.5n have been reported (Allen et al 1986;Benfey et al 1986;Ueda et al 1987Ueda et al , 1991Van Eenennaam et al 1990;Zhang and Arai 1999;Gomelsky et al 2015). Among them, however, meiotic configurations have not been well investigated except for induced triploid Electronic supplementary material The online version of this article (doi:10.1007/s10709-016-9928-8) contains supplementary material, which is available to authorized users.…”
Section: Introductionmentioning
confidence: 99%
“…25I, but induced triploid females could not form fertile eggs (Zhang and Arai 1999). However, it was reported that induced triploid koi (ornamental carp) females spawned fertile eggs and then produced viable aneuploid (mean value 2.6n, range 2.3n to 2.9n) progeny after crossing with diploid males (Gomelsky et al 2015). Unexpected well-developed ovaries were also reported in common carp (Wu 1990;Cherfas et al 1994).…”
Section: Discussionmentioning
confidence: 99%